Pengembangan Model Tes Hasil Belajar Daring Menggunakan Learning Management System (LMS) Berbasis Moodle dalam Pembelajaran Tematik di SD Negeri 17 Pontianak Kota - Nauval Fahrani; Hery Kresnadi; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2023)
This study aims to develop a Moodle LMS-based learning achievement test model for thematic learning at SD Negeri 17 Pontianak Kota. This type of research is development research using the ADDIE model with analysis, design, development, implementation, and evaluation steps. Quantitative data was obtained from the results of product assessments by the validator and from the effects of students filling out the practicality of learning media questionnaires. Qualitative data were obtained from suggestions and notes by the validator and students research instruments in the form of interview guidelines and questionnaires. Learning media's validity level is based on the results of assessments by design and material experts. In contrast, the practicality level of the learning outcomes test model is based on the results of assessments by fifth-grade students at SD Negeri 17 Pontianak City. The validation results by the design expert of the learning outcomes test model obtained an average of 4.9